Fernande Olivier and Pablo Picasso’s advance towards cubism - Mallen, Enrique (Revista Eviterna, 2023)
Marina Picasso wrote about her grandfather’s relationship with his female companions that he «bewitched them, ingested them, and crushed them onto his canvas» (Picasso, 2001, p. 180). What she did not take into account is the fact that those women played a vital role in his creative process, often bringing about major shifts in his career. While we in no way condone his behavior towards the opposite sex, this article concentrates on the crucial impact one of his early life partners, Fernande Olivier, had on his oeuvre as he advanced towards Cubism. Picasso’s style changed as he started living with her in the Bateau-Lavoir, leading to the well-known Rose Period. Fernande’s transformative influence would continue and reach high points during two trips they took together to Spain. As is well known, the young Picasso traveled back home whenever he prepared for a major change in his style. This was definitely the case for these two visits to Gósol in 1906 and Horta in 1909. The first one led to the development of the so-called Iberian period in which Picasso progressively focused on the use of masks, applying them first to Fernande’s features. She would be equally central during their second stay in Spain, when Picasso developed Geometrical Cubism. Again, he projected his discovery onto his companion, as he attempted to merge painting and sculpture when capturing her figure in his canvases.